Peranan Humas dalam Sosialisasi Fungsi dan Tugas Lembaga Tinggi Negara DPD RI : Studi Kasus Sosialisasi Peluncuran Tagline “Dari Daerah untuk Indonesia” pada HUT DPD RI Ke-16 - Kristiyanto, Mas Aryo; Sunarto, Sunarto; Damayanti, Novita (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to determine the role of public relations in the socialization of the functions and duties of the high state institution, DPD RI, and to identify the obstacles faced by public relations in this process. This research also examines the use of media and facilities for socializing the tagline "From the Regions for Indonesia" on the 16th anniversary of the DPD RI. Using a qualitative approach with a case study method, the findings show that public relations plays six key roles: 1) Communicator, bridging two-way communication between the government and the community; 2) Facilitator, absorbing community aspirations and acting as a liaison with policymakers; 3) Disseminator, disseminating information on government policies and activities to both internal and external audiences; 4) Catalyst, influencing public opinion to align with government policies; 5) Counselor, Advisor, and Interpreter, providing advice, translating government policies, and building public trust; and 6) Prescriber, serving as a strategic advisor to leaders in decision-making.